Understanding Pharmaco-Epigenomic Response of Antipsychotic Drugs Using Genome-Wide MicroRNA Expression Profile in Liver Cell Line - Swathy, Babu; Banerjee, Moinak (Frontiers in Molecular Neuroscience, 2022)
Interindividual variability in drug response is a major concern among patients undergoing antipsychotic drug treatment. Apart from genetic and physiological factors, this variability in drug response could also be attributed to epigenetic mechanisms. The microRNAs are key epigenetic markers that plays an important role in pathogenesis and drug response. Several studies have shown that miRNAs are implicated in regulating the expression of various genes involved in drug metabolism and transport. In a conventional clinical setup, it is extremely difficult to distinguish the role of miRNA in pathogenesis and drug response as it is difficult to obtain drug naïve patients. To resolve this issue, we aimed to identify the role of antipsychotic drug treatment in inducing miRNAs expression under an in-vitro condition using a hepatic cell line. A liver cell line was treated with a maximum tolerable drug dosage model for haloperidol, clozapine in monotherapy and their combination in polytherapy. Genomewide miRNA profiling was performed using 60,000 miRNA probes in microarray format in different treatment group. Several miRNAs were observed to be differentially expressed impacting the pharmacokinetic and pharmacodynamic and epigenomic properties upon antipsychotic drug treatment. Interestingly some of these miRNA expression patterns were similar to reported miRNA observations on schizophrenia pathogenesis. The study unravels the potential role of miRNAs in the mechanism of action of antipsychotic drug and could also reflect in drug induced side effects. The study also signifies the importance of pharmacoepigenomic approach while evaluating the role of miRNAs in pathogenesis.